Growth and Development Factors of Infants and Maternal Conditions During Pregnancy for the Eruption of the First Deciduous Teeth (Literature Review): Faktor Pertumbuhan dan Perkembangan Bayi dan Persiapan Kondisi Ibu selama Masa Kehamilan terhadap Erupsi Gigi Desidui Pertama (Tinjauan Pustaka) - Ginting, Rehulina; Tarigan, Yesica Elisabeth (Dentika: Dental Journal, 2022)
Tooth eruption is a condition in which the cusp or incisal of the tooth emerges through the gingiva, but not exceeding 3mm above this level after the corona is formed. The first human tooth that erupts is the mandibular primary central incisor, which is the reference for the eruption of others, including the primary and permanent teeth, that support the growth of the jaw, face, mastication, swallowing, speech, and aesthetics. Furthermore, tooth eruption is influenced by the growth and development of the fetus during pregnancy. Maternal conditions during pregnancy such as age, level of education, physical condition, and nutritional intake affect fetal nutrition which indicates the level of growth and development in the form of head circumference, birth weight, and height that affect the eruption time of the mandibular deciduous central incisor. During pregnancy, the maternal preparation to be considered is the age which might range from 20-35 years, adequate nutritional intake of carbohydrates, folic acid, protein, vitamin C, vitamin D, and minerals, prevention of physical fatigue, intelligence in choosing nutrition, and abstaining from alcohol and caffeine consumption. This study aims to provide information/education on the preparation of pregnant women for the eruption of the mandibular primary central incisor which is part of the infant's growth and development.